PELAKSANAAN PELAYANAN E-KTP DI KECAMATAN BUBUTAN - Saputra, Dwi Aryana (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
IMPLEMENTATION SERVICES E-KTP IN DISTRICT BUBUTAN This thesis entitled "Implementation of E-ktp Services in District Bubutan". The issues raised in this research is how the implementation of E-ID card service in the district lathe, and the extent of the development of such services. The method used in this penelititan is a qualitative research method that is the case study. which focuses intensively on a specific object by studying a case. Qualitative research aims to explain the phenomenon of the deep - inside through data collection. The sampling technique in this research is the snow ball technique (snowball). As the name implies this technique is a technique of determining an initial informant small and then growing more and more because the information submitted by the informant to get informants lain. Qualitative approach, data obtained from the field drawn conclusions that are specific to the general. Data collection techniques used in this research through data reduction, data display, draw conclusions verification. Â Keywords: Publik Service E-KTP